# |
ODE |
Mathematica |
Maple |
\[
{}{y^{\prime \prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = x^{3}+x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = x^{3}+x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = x^{3}+x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y^{\prime \prime \prime }-3 y^{\prime \prime }+5 y^{\prime }-2 y = x \,{\mathrm e}^{x}+3 \,{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }+2 u^{\prime }+u = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y-\sin \left (n x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y-a \cos \left (b x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y-\sin \left (a x \right ) \sin \left (b x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y-4 x^{2} {\mathrm e}^{x^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a^{2} y-\cot \left (a x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+l y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a y^{\prime }+b y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a y^{\prime }+b y-f \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a y^{\prime }+\tan \left (x \right )+b y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-\lambda y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-a^{2} y^{\prime }-{\mathrm e}^{2 a x} \sin \left (x \right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }-3 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }-a^{2} y^{\prime }+2 a^{2} y-\sinh \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 a y^{\prime \prime }+3 a^{2} y^{\prime }-y a^{3}-{\mathrm e}^{a x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+\operatorname {a2} y^{\prime \prime }+\operatorname {a1} y^{\prime }+\operatorname {a0} y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime \prime }-8 y^{\prime \prime }-11 y^{\prime }-3 y+18 \,{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y-f = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+\lambda y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-12 y^{\prime \prime }+12 y-16 x^{4} {\mathrm e}^{x^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 a^{2} y^{\prime \prime }+a^{4} y-\cosh \left (a x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+\left (\lambda +1\right ) a^{2} y^{\prime \prime }+\lambda \,a^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-3 y^{\prime \prime }-4 y^{\prime }+4 y-32 \sin \left (2 x \right )+24 \cos \left (2 x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime \prime \prime }-12 y^{\prime \prime \prime }+11 y^{\prime \prime }-3 y^{\prime }-4 \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}f \left (y^{\prime \prime \prime \prime }-2 a^{2} y^{\prime \prime }+a^{4} y\right )+2 \operatorname {df} \left (y^{\prime \prime \prime }-a^{2} y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}f y^{\prime \prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+2 y^{\prime \prime \prime }+y^{\prime }-a x -b \sin \left (x \right )-c \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}+y-\sin \left (\frac {3 x}{2}\right ) \sin \left (\frac {x}{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+a y^{\prime \prime \prime \prime }-f = 0
\] |
✓ |
✓ |
|
\[
{}x \left (a y^{\prime }+b y^{\prime \prime }+c y^{\prime \prime \prime }+e y^{\prime \prime \prime \prime }\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime } y^{\prime \prime \prime }-3 {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a y^{\prime }+b y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime \prime }-3 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }-y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-2 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+9 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }-2 y^{\prime } = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{{\mathrm e}^{x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = 2 \,{\mathrm e}^{-x}-x^{2} {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{\left (1-x \right )^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }-y^{\prime }+3 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sec \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime \prime }+5 y^{\prime }-2 y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sec \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = x^{2}+\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 2 \,{\mathrm e}^{2 x} x -\sin \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 2 \,{\mathrm e}^{x}+x^{3}-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 3 \,{\mathrm e}^{2 x}-\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }-3 y^{\prime } = 3 x^{2}+\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime }+y = {\mathrm e}^{x}+4
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime } = 1+{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = \cos \left (x \right )-{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = {\mathrm e}^{x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 2 x^{3}-x \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|